“Escole” : Intervention program for the attention in the deficit of reading comprehension - Culqui Poclin, Rosario Franshesca (2020)
The deficit of reading comprehension is a problem that is evident in students from primary level and even up to higher level. The ESCOLE project proposes various strategies to improve the levels of reading comprehension (literal, inferential, and reflective) based on the recreation and dramatization of short Peruvian stories: Paco Yunque and El Niño de Along the Sky.This program develops an integrated intervention in coordination with all educational agents. Its purpose is to carry out activities that allow students to enhance reading skills that include all the levels required for comprehension. That is to say, it is intended to develop their capabilities in a comprehensive way so that they become competent in all academic areas.ESCOLE is aimed at students in the first year of secondary education; however, it can be applied to any human group, as it is versatile, entertaining and does not require sophisticated materials for its execution.